Genes associated with rheumatoid arthritis and mild inflammatory arthritis. I. Major histocompatibility complex class I, II, and III allotypes. Issue 4 (April 1990) - Puttick, A H; Briggs, D C; Welsh, K I; Vaughan, R; Williamson, E A; Boyce, M; Jacoby, R K; Jones, V E
Abstract : Patients with mild inflammatory arthritis (IA) were compared with patients with definite rheumatoid arthritis (RA) for abnormal frequencies of major histocompatibility complex (MHC) antigens and haplotypes to determine whether a genetic predisposition either to RA or to mild self-limiting arthritis/arthralgia was present in the patients with IA. In general the MHC antigens with abnormal frequencies found in patients with IA differed from those in patients with RA and were mainly at the A and B loci. In patients with IA the frequencies of HLA-A24, A25, B27, and B35 antigens were significantly higher than those of controls and HLA-DR5 and C4A4 were slightly raised. In contrast, in patients with RA abnormal frequencies of the MHC antigens DR4 and DR2 and the extended haplotypes associated with them [B62 BfS C4A3 C4B3 DR4 GLO2] and [B7 BfS C4A3 C4B1 DR2] confirmed the observations reported on other white populations. Thus MHC antigen associations with IA and RA differ sufficiently to suggest a different genetic basis for the two conditions.